Liuzijue training improves hypertension and modulates gut microbiota profile - Wu, Sha; Zheng, Caiping; Liu, Nannan; Deng, Tingting; Wang, Jie; Qi, Luming; Xia, Lina (Frontiers in Cardiovascular Medicine, 2023)
Background Liuzijue training (LZJ) is a traditional exercise integrating breathing meditation and physical exercise, which could prevent and improve hypertension symptoms. Purpose We aimed to evaluate the therapeutic effect of LZJ on hypertensive patients from the perspectives of blood pressure (BP), vascular endothelial function, immune homeostasis, and gut microbiota. Methods We conducted a randomized, controlled, single-blind experiment to assess the effect of 12 weeks LZJ in hypertensive patients. We measured the blood pressure level, vascular endothelial function, serum inflammatory factor concentration, and fecal microbial composition of hypertension patients. Results Compared with aerobic training, LZJ has a more significant effect on serum inflammatory factors (IL-6 and IL-10) and gut microbiota. PCoA analysis showed that LZJ tended to transform the gut microbiota structure of hypertensive subjects into that of healthy people. This process involves significant changes in Bacteroides, Clostridium_sensu_stricto_1, Escherichia-Shigella, Haemophilus, Megamonas, and Parabacteroides. In particular, Bacteroides and Escherichia-Shigella, these bacteria were closely related to the improvement of BP in hypertensive patients. Conclusion In conclusion, our results confirm that LZJ could be used as an adjuvant treatment for hypertensive patients, which could effectively reduce BP, improve the immune homeostasis and gut microbiota structure in patients, and provide a theoretical reference for the use of LZJ in the clinic. Clinical trial registration http://www.chictr.org.cn/listbycreater.aspx, identifier: ChiCTR2200066269.